A novel costimulatory molecule gene-modified leukemia cell-derived exosome-targeted CD4+ T cell vaccine efficiently enhances anti-leukemia immunity - Li, Jiaqi; Huang, Fang; Jiang, Yan; Zhao, Jie; Wan, Jiangbo; Hao, Siguo (Frontiers in Immunology, 2022)
Previous studies demonstrated that CD4+ T cells can uptake tumor antigen-pulsed dendritic cell-derived exosomes (DEXO), which harbor tumor antigen peptide/pMHC I complex and costimulatory molecules and show potent effects on inducing antitumor immunity. However, in preliminary study, CD4+ T cells targeted by leukemia cell-derived exosomes (LEXs) did not show the expected effects in inducing effective anti-leukemia immunity, indicating that LEX is poorly immunogenetic largely due to an inadequate costimulatory capacity. Therefore, LEX-based anti-leukemia vaccines need to be optimized. In this study, we constructed a novel LEX-based vaccine by combining CD4+ T cells with costimulatory molecules gene-modified LEXs, which harbor upregulated CD80 and CD86, and the anti-leukemia immunity of CD80 and CD86 gene-modified LEX-targeted CD4+ T cells was investigated. We used lentiviral vectors encoding CD80 and CD86 to successfully transduced the L1210 leukemia cells, and the expression of CD80 and CD86 was remarkably upregulated in leukemia cells. The LEXs highly expressing CD80 and CD86 were obtained from the supernatants of gene-transduced leukemia cells. Our data have shown that LEX-CD8086 could promote CD4+ T cell proliferation and Th1 cytokine secretion more efficiently than control LEXs. Moreover, CD4+ TLEX-CD8086 expressed the acquired exosomal costimulatory molecules. With acquired costimulatory molecules, CD4+ TLEX-CD8086 can act as APCs and are capable of directly stimulating the leukemia cell antigen-specific CD8+ CTL response. This response was higher in potency compared to that noted by the other formulations. Furthermore, the animal study revealed that the CD4+ TLEX-CD8086 significantly inhibited tumor growth and prolonged survival of tumor-bearing mice than other formulations did in both protective and therapeutic models. In conclusion, this study revealed that CD4+ TLEX-CD8086 could effectively induce more potential anti-leukemia immunity than LEX-CD8086 alone, suggesting that the utilization of a costimulatory molecule gene-modified leukemia cell-derived exosome-targeted CD4+ T cell vaccine may have promising potential for leukemia immunotherapy.